Telomere Dysfunction in Idiopathic Pulmonary Fibrosis - Zhang, Kexiong; Xu, Lu; Cong, Yu-Sheng (Frontiers in Medicine, 2021)
Idiopathic pulmonary fibrosis (IPF) is an age-dependent progressive and fatal lung disease of unknown etiology, characterized by the excessive accumulation of extracellular matrix inside the interstitial layer of the lung parenchyma that leads to abnormal scar architecture and compromised lung function capacity. Recent genetic studies have attributed the pathological genes or genetic mutations associated with familial IPF and sporadic IPF to telomere-related components, suggesting that telomere dysfunction is an important determinant of this disease. Here, we summarize recent advances in our understanding of how telomere dysfunction drives IPF genesis. We highlight the key role of alveolar stem cell dysfunction caused by telomere shortening or telomere uncapping, which bridges the gap between telomere abnormalities and fibrotic lung pathology. We emphasize that senescence-associated secretory phenotypes, innate immune cell infiltration, and/or inflammation downstream of lung stem cell dysfunction influences the native microenvironment and local cell signals, including increased TGF-β signaling in the lung, to induce pro-fibrotic conditions. In addition, the failed regeneration of new alveoli due to alveolar stem cell dysfunction might expose lung cells to elevated mechanical tension, which could activate the TGF-β signaling loop to promote the fibrotic process, especially in a periphery-to-center pattern as seen in IPF patients. Understanding the telomere-related molecular and pathophysiological mechanisms of IPF would provide new insights into IPF etiology and therapeutic strategies for this fatal disease.